No food security, no world order (2020)
While food insecurity and malnutrition remain significant challenges, over the last two decades, the global hunger rate decreased 25%.1 Much of that decline is attributed to decreases in poverty. In the last 30 years, populations living in extreme poverty (defined as those living on less than $1.90 per day) decreased from 2 billion in 1990 to 700 million in 2015. These gains have in large part been attributed to stronger social protection programs, increased basic service coverage, and income and private sector growth. However, in the last four years, the number of people who go to bed hungry has risen from 796 million to 821 million.2 Immediate or acute hunger increased by 70% over the same period, from 80 million to 135 million, with the majority of those populations living in Africa or conflict-affected countries.3 Why has hunger increased, undermining years of progress? Most of the rise is due to climate change and conflict.4 Sixty percent of people facing hunger live in war-torn countries such as Afghanistan, the Democratic Republic of Congo (DRC), Nigeria, Syria, Venezuala, and Yemen.5 Climate change, too, has played a significant role; climate-related natural disasters have significantly tested the efficiency and functioning of global food systems.